Financial Innovation and Information: The Role of Derivatives When a Market for Information Exists - Massa, Massimo (Review of Financial Studies, 2002)
We study the effects of financial innovation in a model of endogenous information acquisition. We determine the conditions under which the introduction of a derivative written on an existing stock increases or decreases the incentive to purchase information. We show that financial innovation produces some effects which hold across informational structures and others which differ. The former coincide with the few empirical results that are robust in the literature (effects on prices, risk premia, and volatility), while the latter coincide with the ones that differ experiment by experiment (effects on volume, correlation between volume and volatility, and market informational efficiency).